Incidence and associated risk factors for invasive fungal infections and other serious infections in patients on ibrutinib. Issue 12 (December 2021) - Holowka, Thomas; Cheung, Harry; Malinis, Maricar; Gan, Geliang; Deng, Yanhong; Perreault, Sarah; Isufi, Iris; Azar, Marwan M.
Abstract: Background: Ibrutinib is a small molecule tyrosine kinase inhibitor that blocks the activity of B cells and other immune effectors and is used in a variety of hematologic malignancies. There have been numerous reports of increased frequency of serious infections including invasive fungal infections (IFI) in patients on ibrutinib. Methods: Demographic and clinical features of all patients receiving ibrutinib at a single tertiary care center were collected from electronic medical records. Univariate and multivariate statistical analyses were performed to find out the factors associated with infection. Results: A total of 244 patients received ibrutinib for hematologic malignancies, of which 44 (18.0%) experienced ≥ 1 serious infection including 5 (2.0%) with IFI (1 pulmonary cryptococcosis, 4 pulmonary aspergillosis), 39 (16.0%) with bacterial infections and 8 (3.3%) with viral infections. Ten patients (4.1%) experienced multiple infections or co-infections while on ibrutinib and 10 (4.1%) expired or were transferred to hospice as a result of infection. In multivariate analysis risk factors that were less common in uninfected versus infected patients included advanced age (73 years vs. 77 years), Eastern Cooperative Oncologic Grade (ECOG) performance score ≥ 2 (6.5% vs. 31.8%) and concurrent use of steroids (4.5% vs. 20.5%) or other cytotoxic agents (0% vs. 4.6%). Conclusions: There was a high rate of serious infection but relatively few IFI in patients receiving ibrutinib. Most patients who developed serious infections while on ibrutinib had additional predisposing risk factors including concurrent use of steroids or other cytotoxic agents, advanced age and frailty.